Թանկարժեք քարերը և դրանց բուժական հատկությունները ըստ միջնադարյան աղբյուրների - Մոսիկյան, Կարինե
Many works of ancient and medieval authors were devoted to the secrets of the origin of stones and their use in medical practice. Works of a similar nature have also been found in many Armenian manuscripts. The most popular among them was Epiphanius’ work on the twelve stones of Aaron's breastplate. There also occur works bearing the title On Precious Stones by unknown authors as well as and well- known scientists: Mkhit‘ar Herats‘i, Asar Sebastas‘i, Aṛak‘el Davrizhets‘i, Anania Shirakats‘i, and others. A comparative study of gemstones through these works sheds light on this ancient field of study, interest in which has persisted until the present day. Тайнам происхождения камней и их использованию в медицинской практике были посвящены многие труды античных и средневековых авторов. Во многие армянские рукописи также включали сочинения аналогичного содержания. Среди этих произведений наибольшей популярностью пользовалась работа Епифания Кипрского о двенадцати камнях нагрудника Аарона. Также часто встречаются сочинения, озаглавленные «О драгоценных камнях»; они принадлежат перу известных армянских средневековых эрудитов: Мхитара Гераци, Асара Себастаци, Аракела Даврижеци, Анании Ширакаци и др. Сравнительное изучение учений о драгоценных камнях в этих произведе- ниях проливает свет на этот уходящий в глубь веков, но все еще живой интерес к этому предмету.
Keywords: Բնագիտություն